2010
DOI: 10.1002/ana.22095
|View full text |Cite
|
Sign up to set email alerts
|

Use of guidelines improves the neurological outcome in glutaric aciduria type I

Abstract: Follow-up of neonatally diagnosed patients with GA-I in Germany clearly demonstrates that the inclusion of this rare disease in the NBS disease panel has significantly improved the neurological outcome of affected individuals. The establishment of and adherence to evidence-based treatment recommendations, and supervision by experienced metabolic centers helps to minimize the number of patients who do not benefit from NBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
226
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(239 citation statements)
references
References 30 publications
6
226
0
7
Order By: Relevance
“…In our study, we did not perform any follow-up MRI. It has been shown (Heringer et al 2010) that prompt vigorous intervention during acute episodes with the provision of glucose, fluids and electrolytes along with carnitine supplementation can prevent striatal degeneration and has improved outcome. Most of our patients had acute crises prior to the diagnosis.…”
Section: Clinical Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we did not perform any follow-up MRI. It has been shown (Heringer et al 2010) that prompt vigorous intervention during acute episodes with the provision of glucose, fluids and electrolytes along with carnitine supplementation can prevent striatal degeneration and has improved outcome. Most of our patients had acute crises prior to the diagnosis.…”
Section: Clinical Spectrummentioning
confidence: 99%
“…Extrapyramidal symptoms are due to bilateral striatal injury during the acute episode. Early diagnosis and prompt initiation of treatment can prevent the long-term complications and mortality which have led to its inclusion in conservative newborn screening programs (Heringer et al 2010;Kolker et al 2007). GCDH enzyme is encoded by GCDH gene, which is located on the chromosome 19p13.2 spanning about~7 kb and contains 12 exons (Transcript ID ENST00000222214) and encodes 438 amino acid-long precursor protein.…”
Section: Introductionmentioning
confidence: 99%
“…It also serves to highlight that thorough biochemical evaluation with chromatographic analysis of urine organic acids in asymptomatic or paucisymptomatic children or adolescents with macrocephaly will prevent diagnostic delay in GA-I and may prove vital for prognosis (Heringer et al 2010). Although our case escaped the severe dystonic encephalopathy associated with GA-I, this is a rare occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although our case escaped the severe dystonic encephalopathy associated with GA-I, this is a rare occurrence. Thus, early diagnosis of GA-I and prompt implementation of appropriate dietary, therapeutic, and preventive measures can dramatically improve prognosis for this treatable inborn error of metabolism (Heringer et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies reported substantial improvement in quality both in inpatient [1,11,14,18,21,32,50,53,57,60,62,68,78] and outpatient settings [13,29,37,40,42,46]. Numerous studies, including six RCTs [4,7,38,51,63,71], failed to show any positive effects on quality associated with practice guidelines [5,10,20,25,26,36].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%